SMART ANDON SYSTEM BASED ON INDUSTRIAL INTERNET OF THINGS (IIOT) - Purnomo , Wahyudi; Maulana, Gun Gun; Suryatini, Fitria; Sunarya, Adhitya Sumardi (Jurnal Rekayasa Mesin, 2024)
In many industrial settings, there are several problems that can arise during the production process. These include machine breakdowns, quality issues, and unexpected delays, which can impact productivity, reduce overall efficiency, and result in lower quality output. In addition, without an effective monitoring system, it can be difficult to identify the root causes of these problems and take appropriate corrective actions.To address these challenges, the implementation of a smart andon system can be highly beneficial. This system enables real-time monitoring of the production process, allowing operators and management to quickly identify and respond to any issues as they arise. By providing instant notifications and alerts, the smart andon system can help reduce downtime, increase productivity, and improve product quality. It also enables more accurate and comprehensive data collection, facilitating better analysis and decision-making by management. Overall, the smart andon system can play a critical role in improving operational efficiency, reducing costs, and enhancing overall competitiveness in today's highly competitive industrial landscape.the implementation of a smart andon system has been shown to improve production efficiency, reduce downtime, and increase overall equipment effectiveness (OEE). The system allows for real-time monitoring of the production process, early detection of problems, and quick resolution of issues through timely alerts and notifications. This can result in significant cost savings for the industry, improved product quality, and increased customer satisfaction.